Profile of Students' Creative Thinking Skills on Quantitative Project-Based Protein Testing using Local Materials (Jurnal Pendidikan IPA Indonesia, 2017)
The purpose of this study is to obtain a profile of students’ creative thinking skills on quantitative project-based protein testing using local materials. Implementation of the research is using quasi-experimental method pre-test post-test control group design with 40 students involved in Biochemistry lab. The research instrument is pre-test and post-test using creative thinking skills in the form of description and students’ questionnaire. The analysis was performed with SPSS 22.0 program to see the significance normality, U Mann-Whitney test for nonparametric statistics, N-Gain score, and the percentage of student responses to the practicum performed. The research result shows that the pretest rate in the experimental group is 8.25 while in the control group is 6.90. After attending a project-based practicum with local materials, the experimental group obtained the mean of posttest is 37.55 while in control class is 11.18. The students’ improvement on creative thinking skills can be seen from the average of N-Gain in the experimental class with 0.32 (medium category) and in the control category with 0.05 (low category). The experimental and control class have different creative thinking skills significantly different fluency, flexibility, novelty, and detail. It can be concluded that quantitative project-based protein testing using local materials can improve students’ creative thinking skills. 71% of total students feel that quantitative project-based protein testing using local materials make them more creative in doing a practicum in the laboratory.